Penerapan Akuntabilitas dan Transparansi Pengelolaan Alokasi Dana Desa dalam Pembangunan Infrastruktur Desa (Studi di Desa Tanggung Kecamatan Turen Kabupaten Malang) - Devina Ardiany, Della; Hayat, Hayat; Dwi Rahmawati, Septina (LP3M, Universitas Muhammadiyah Kendari, 2023)
Accountability is a form of accountability carried out by the government as reporting on activities carried out to the public. This accountability is the ground for the implementation of transparency in every implementation of activities. This study aims to assess and determine accountability and transparency in the management of village fund allocations carried out by the village government of Responsibility, Turen District, Malang Regency. The approach used in this research is descriptive qualitative. The data collection technique used was interviews involving the Village Government and village communities, totaling four informants. The results of this study indicate that, starting with accountability and transparency, managing village financial allocations for village infrastructure development under the responsibility as a whole is adequate, but still has some drawbacks. This is demonstrated by the application of the principle of government accountability in managing village fund allocations, in particular by involving the community in planning village fund allocations, but only until the rest of the planning is carried out by the village government without involving village officials in managing village funds. Thus, it is claimed that the implementation of transparency in managing village fund allocations in Responsibility Villages is not good. This is because the government does not apply the principle of transparency, especially by not fully involving the members of the village in managing village funds and by managing village funds in an opaque manner. Therefore it is claimed that the implementation of transparency in accordance with the implementation of the three processes is not good.